Hukum Administrasi Negara Sebagai Alat Mewujudkan Kesejahteraan Sosial Dalam Perspektif Negara Demokrasi - Karisma Putri Tri Sutanti (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This research aims to analyze the role of state administrative law in realizing social welfare within the framework of a democratic state and the challenges faced in its implementation in Indonesia. The method used is descriptive research with a qualitative approach, which focuses on descriptions of laws and regulations, policy analysis, and evaluation of challenges and solutions related to the implementation of state administrative law. The research results show that state administrative law plays a crucial role in ensuring the implementation of government and public services that are effective, fair and responsive. Law Number 30 of 2014 concerning Government Administration and Law Number 25 of 2009 concerning Public Services are the fundamental legal basis for realizing the principles of transparency, accountability and community participation. However, the implementation of state administrative law often faces challenges such as complicated bureaucracy, lack of resources, legal uncertainty, and lack of coordination between agencies. To overcome these challenges, this research recommends several solutions, including simplifying bureaucratic processes, increasing resource capacity, legal certainty and simplifying regulations, strengthening inter-agency coordination, and increasing community participation. In addition, efforts to eradicate corruption, develop infrastructure, and increase transparency and accountability are also considered important to increase the effectiveness of implementing state administrative law and achieve social welfare. This research aims to provide applicable policy recommendations to improve the state administration system in Indonesia.